Gambaran Transtheoritical Model pada Mahasiswa Pasca Apendiktomi (Setelah Operasi Usus Buntu) - Rizkitara, Rinanti Dwi; Koto, Dicky Febrian (Lembaga Yasin AlSys, 2024)
Appendicitis has become a current health issue, the World Health Organization (WHO) estimates that appendicitis is at the eighth level as a disease that can cause death in 2020. One way to cure appendicitis is by carrying out surgery. Appendicitis patients who have had an appendectomy should not consume foods that are high in fat, spicy foods, and foods high in sugar. Behavioral changes that focus primarily on a person's ability to make decisions from social and biological influences are called the Tarnstheoretical Model (Porchaska & Velicer, 1997). The aim of this research is to see what the transtheoretical model looks like for post-appendectomy students. The type of research used in this research is descriptive analysis with a quantitative approach. The population in this study were Padang State University students. The sampling technique used in this research was non-probability sampling with a purposive sampling method with a total of 34 respondents. The measuring instrument used is a questionnaire prepared based on the Transtheoretical Model theory. The results of this study show that 68% of post-appendectomy students in the transtheoretical model are in the high category.